Use of calcium carbonate-nanoparticle-longkong peel extract in edible coating to delay longkong fruit browning - Lichanporn I.,; Nantachai N.,; Tanganurat P., (Penerbit Universiti Kebangsaan Malaysia, 2019)
The effect of calcium carbonate (CaCO3)-nanoparticle-longkong peel extract (LPE) coating on quality and browning of longkong after harvesting were evaluated. Edible coating (carrageenan) was used as a component of 1 mM CaCO3 and 2.00 mg LPE. Longkongs were coated with 0 (control), 1 and 2% carrageenan and storing them at 13°C and 90-95% RH for 14 days. Longkong were analyzed for changes in browning pigment, L* value, pH, total phenolic content, polyphenol oxidase (PPO) and total sugar. The results showed longkong coating with 1 and 2% carrageenan (CGN) lower browning pigment, which correlated with a decrease in PPO and total phenolic content than control. However, longkong coating with 1% CGN delayed browning more than longkong coating 2% CGN during ten days of storage. While the sugar was significantly higher in control compared to 1 and 2% CGN. Longkong treated with 1 and 2% CGN showed no significantly a decrease in pH when compared to the control fruit.